Pengaruh Profitabilitas, Solvabilitas, Dan Likuiditas Terhadap Penghindaran Pajak Dimoderasi Oleh Political Connection Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Rumbi, Yesaya Bittikaka; Syamsuddin, Syamsuddin; Pontoh, Grace T. (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
Tax plays an important role in the realization of state revenue. For the benefit of the state, tax is the largest source obtained by the state from the contribution of taxpayers. Companies usually look for ways to reduce tax payments legally or illegally because their goal is to maximize profits. Therefore, companies usually do tax avoidance. This study aims to test and analyze the effect of profitability, solvency, and liquidity on tax avoidance moderated by political connections. This study was conducted on manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. This study uses a quantitative method with multiple linear regression analysis tools and moderate regression analysis. The sampling method uses purposive sampling with a sample size of 69 companies during 2020-2022. The results of this study indicate that partial profitability has a negative and significant effect on tax avoidance, solvency has a positive and significant effect on tax avoidance, liquidity has a negative and significant effect on tax avoidance, profitability has a positive and significant effect on tax avoidance moderated by political connections, solvency has a negative and significant effect on tax avoidance moderated by political connections, liquidity has a positive and significant effect on tax avoidance moderated by political connections. Profitability, solvency, and liquidity together have a significant effect on tax avoidance moderated by political connections. This indicates that profitability, solvency, and liquidity moderated by political connections can increase tax avoidance.